Audit Internal Sebagai Upaya Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Keuangan Bumdes di Desa Pematang Serai, Tanjung Pura : Penelitian - Yulisfan Yulisfan; Irsan Nasution; Ahmad Braja Bayu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Accountable and transparent financial management of Village-Owned Enterprises (BUMDes) is crucial for business sustainability and public trust, yet many BUMDes lack adequate internal audit and control systems. This community service program aims to strengthen BUMDes financial governance through the implementation of a simple, participatory, and village-specific internal audit system. The program was conducted in Pematang Serai Village, Tanjung Pura District, Langkat Regency, involving BUMDes administrators, village officials, and the community. The methods used included outreach, group discussions, mentoring in the development of internal audit systems and financial SOPs, and the implementation of internal audits. The results demonstrated an increase in administrators' understanding and skills in recording transactions, preparing financial reports, and internal audits. The program also produced documents on internal audit systems, SOPs, and sustainable financial reporting formats. The program also increased community participation and awareness of transparency and accountability, leading to more open and responsible BUMDes financial management.